2024
DOI: 10.1186/s13287-024-03639-x
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic human MSC-derived extracellular vesicles regulate MSC activity and osteogenic differentiation and promote bone regeneration in a rat calvarial defect model

Niyaz Al-Sharabi,
Samih Mohamed-Ahmed,
Siddharth Shanbhag
et al.

Abstract: Background There is growing evidence that extracellular vesicles (EVs) play a crucial role in the paracrine mechanisms of transplanted human mesenchymal stem cells (hMSCs). Little is known, however, about the influence of microenvironmental stimuli on the osteogenic effects of EVs. This study aimed to investigate the properties and functions of EVs derived from undifferentiated hMSC (Naïve-EVs) and hMSC during the early stage of osteogenesis (Osteo-EVs). A further aim was to assess the osteoind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Moreover, in vivo models showing a positive effect of exosomes on bone regeneration are mainly rodent-based [53,54]. The limitation of this research for small animal studies has already been reported, and further efforts are recommended to progress the research to large animal studies [55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vivo models showing a positive effect of exosomes on bone regeneration are mainly rodent-based [53,54]. The limitation of this research for small animal studies has already been reported, and further efforts are recommended to progress the research to large animal studies [55].…”
Section: Discussionmentioning
confidence: 99%